PERAN STRESOR HARIAN, OPTIMISME DAN REGULASI DIRI TERHADAP KUALITAS HIDUP INDIVIDU DENGAN DIABETES MELITUS TIPE 2 - Kusumadewi, Melina Dian (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2011)
The aim of this research is to analyze the role of daily stress, optimsm and self regulation  toward the quality of life of type 2 individual with diabetic mellitus. The hypothesis of this research are: 1). There is a negative relationship between daily stress and quality of life; 2). Optimsm as moderate relation between daily stress and quality of life; 3). Autonom self regulation as moderate relation between daily stress and quality of life; 4). Controlled self regulation as mediator relation daily stress and quality of life. Research Methodology: The research is conducted among individuals who were diagnosed with type 2 diabetic mellitus in Sardjito Hospital Yogyakarta. There are 64 subjects who completed the research tools (daily stress, optimism, self regulation and quality of life scale) started from January 4th– February 12 2010. The research shows that there is a  negative relation between daily stress and quality of life (r = 0,265; F = 22,304; p = 0,000; p 0,01; significant). The result of moderate regression analysis shows optimsm is not moderate variable, but autonom self regulation is moderate variable (β = 0,004; p 0,001; significant). The result of path analysis shows that controlled self regulation is mediator relation of daily stress and quality of life (p = 0,045; p 0,05; significant). There is a negative significant relation between daily stress and quality of life. Optimism is not significant as moderate variable relation between daily stress and quality of life. Autonom regulation is significant as moderate relation between daily stress and quality of life. Controlled self regulation is significant as mediator relation of daily stress and quality of life.